Does Shareholder Concentration Matter In Small And Medium Enterprises (SMEs)? : Empirical Evidence From SMEs In Manufacturing Sector In Northern Corridor Economic Region (NCER) - Lim, Kent Soon. (2009)
Given the important role of SMEs as a growth factor in local economy, ensuring a strong and competitive development for this industry segment has become a key concern in making the Northern Corridor Economic Region (NCER) a success. Memandangkan peranan penting yang dimainkan oleh Perusahaan Kecil and Sederhana (PKS) dalam pertumbuhan ekonomi negara, satu daya saingan yang kuat diperlukan oleh industri ini demi menjayakan Wilayah Ekonomi Koridor Utara (NCER).